(untitled) - Biggam, John (New York, 2011)
This popular book continues to demystify the dissertation writing process. Taking a step-by-step approach to the dissertation life cycle and highlighting examples of good and bad practice and the common mistakes that students often make, the book provides clear guidance on how to gain marks, as well as how to avoid losing them.
Keywords: Luận văn, học thuật,Kỹ năng viết,Dissertations, academic,Writing skills; Quyền tác giả,Authorship